ANALISIS PENERAPAN SAK EMKM PADA LAPORAN KEUANGAN UMKM DI KOTA BATAM - Liasari, Priskila Ajoe; Wage, Sunarto ` (LPPM Universitas Putera Batam, 2021)
Seeing-the-importance-of the application of accounting standards for “UMKM”, IAI as the body of preparation of Financial Accounting Standards (SAK) through the Financial Accounting Standards Board (DSAK) which develops accounting standards in accordance with the characteristics of “UMKM”. In 2016, DSAK has endorsed SAK EMKM (Small and Medium Enterprises) and is effective as of January 1, 2018. The purpose of this research is (1) To find out the bookkeeping process carried out on a number of “UMKM” in “Batam Kota” District, (2) To find out the suitability between bookkeeping of financial statements in “UMKM” in “Batam Kota” District with SAK EMKM,(3) To know the constraints in doing the appropriate bookkeeping SAK EMKM on “UMKM” in “Batam Kota” District. In accordance with the purpose of this research, this research uses descriptive qualitative research methods. Data analysis in this study uses descriptive analysis, which is clearly described the results of research based on data obtained directly and compiled with established standards, Based on the results of research can be concluded that, (1) Bookkeeping conducted on “UMKM” is still limited to business reports that are reports that are compiled not in accordance with financial accounting standards, but entities consider it as financial statements. (2) There are still many entities that have not performed bookkeeping procedures in accounting. (3) “UMKM” have not implemented SAK-EMKM. (4) The Entity has not been able to present financial statements in accordance with SAK-EMKM.